Hubungan antara Kebermaknaan Hidup dengan Kemandirian pada Remaja - Erfiana, Lina Ria (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstrakThis study aimed to determine the relationship between the meaningfulness of life with independence in adolescents. The subjects were students of class XI of SMAN 1 Prambanan Sleman Yogyakarta. Data collection methods used in this research is the scale, the scale and the scale independence of the meaningfulness of life. Analysis using Pearson´s correlation technique of Product Moment and computational assistance statisiic 18.00 SPSS for Windows. The results showed that there was a significant relationship between the variable to an independent variable meaningfulness of life in adolescents. The relationship is shown by the correlation coefficient r = 0.497 with a significance level of 0.000 (p <0.01). Categorization results showed 115 study subjects are 60.87% have a independence in the medium category, 68.7% have less meaningfulness of life in the medium category. Based on the data analysis we concluded that there was a significant relationship between the variable to an independent variable meaningfulness of life in adolescents.Keywords: MeaningÂ  of Life and independent.